PENGARUH CAREER DEVELOPMENT TERHADAP SUCCESSION DENGAN EFEK MEDIASI ORGANIZATIONAL JUSTICE PADA PT SUMBERDAYA SEWATAMA - Ariza, Florentino; Purba, Sylvia Diana (Jurnal Manajemen, 2015)
This research was conducted in order to determine whether the Organizational Justice has a mediating effect in the influence of Career Development to Succession in a family enterprise in the research, namely PT SumberdayaSewatama. The sampling method used is convenience sampling. This research took a sample of 38 employees at managerial level. Methods of data analysis used in this research is the analysis of the effect of mediation (OJ) and test effect of independent variables (CD) to the dependent variable (S). The results of data processing using SPSS 22 for windows with macros and hayes 2013. The result shows that managerial level employees at PT Sumberdaya Sewatama have career development, organizational justice, and succession were already good, but organizational justice can not mediate the effect of career development to succession.Keywords: Career Development, Succession, and Organizational Justice